Dire fare... baciare! Emozionarsi giocando - Nesti, Romina (Studi sulla Formazione/Open Journal of Education, 2017)
This paper promotes reflections about game as tool of emotional education. The game is search of emotions, emotions that only in the game express themselves, emotions that only in the game can be lived without fear. The paper focuses on the role of the adult and the design of the game environment.